Collaborative models for adaptive conservation in the Ethiopian Highlands - Steger, Cara, author (Colorado State University. Libraries, 2017)
My dissertation seeks to advance our understanding of collaborative governance to improve the management of complex social-ecological systems. Modeling is increasingly used to facilitate collaborative environmental governance, yet little research has been done to measure the impacts of this process on local ecological knowledge, cultural norms, and cultural values. My research investigates the cultural and cognitive changes that occur when participants engage with a scientific modeling process. This case study on technologically-mediated cultural change has potential to inform the study and implementation of collaborative methods for advancing adaptive and resilient social-ecological systems worldwide.
278 - Cara Elizabeth Steger